Regulatory function of the Saccharomyces cerevisiae RAS C-terminus. - Marshall, M S (1987)
Activating mutations (valine 19 or leucine 68) were introduced into the Saccharomyces cerevisiae RAS1 and RAS2 genes. In addition, a deletion was introduced into the wild-type gene and into an activated RAS2 gene, removing the segment of the coding region for the unique C-terminal domain that lies between the N-terminal 174 residues and the penultimate 8-residue membrane attachment site. At low levels of expression, a dominant activated phenotype, characterized by low glycogen levels and poor sporulation efficiency, was observed for both full-length RAS1 and RAS2 variants having impaired GTP hydrolytic activity. Lethal CDC25 mutations were bypassed by the expression of mutant RAS1 or RAS2 proteins with activating amino acid substitutions, by expression of RAS2 proteins lacking the C-terminal domain, or by normal and oncogenic mammalian Harvey ras proteins. Biochemical measurements of adenylate cyclase in membrane preparations showed that the expression of RAS2 proteins lacking the C-terminal domain can restore adenylate cyclase activity to cdc25 membranes.